HEPATOPROTECTIVE ACTIVITY OF SPHAERANTHUS AMARANTHOIDES WHOLE PLANT IN PARACETAMOL INDUCED HEPATOTOXICITY IN RATS - Gowri, Radhakrishnan; Madhavan, Varadharajan; Yoganarasimhan, Sunkam (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: To evaluate the protective effect of ethanol extract of whole plant of Sphaeranthus amaranthoides against paracetamol induced hepatotoxicity in albino wistar rats. Methods: Liver damage was induced by administration of paracetamol orally at a dose of 2 g/kg body weight. Protective effect of the extract was determined by assessing the levels of serum enzymes like AST, ALT, ALP, total protein, total bilirubin, liver Malondialdehyde and glutathione levels. The extract was standardized by HPTLC method. Results: Administration of ethanol extract at 400 mg/kg b. wt showed significant (***P<0.001) reduction in elevated serum enzyme levels compared to paracetamol induced animals. Paracetamol induced liver toxicity decreased the liver glutathione level and increased the MDA level. The results of our study showed that ethanol extract at 400 mg/kg significantly increased glutathione content and decreased the MDA level indicating the protective role of Sphaeranthus amaranthoides ethanol extract against paracetamol induced liver toxicity. Conclusion: Sphaeranthus amaranthoides whole plant possesses potent hepatoprotective activity against paracetamol induced hepatotoxicity. Â